PENGATURAN HUKUM INTERNASIONAL MENGENAI BIOTEKNOLOGI DAN DAMPAKNYA TERHADAP KEANEKARAGAMAN HAYATI - Friska Messelina Sirait; Suhaidi Suhaidi; Jelly Leviza (Journal of USU International Law, 2013)
Abstract Biotechnology in human's life gives a new expectation of an ability to create new organisms. Biotechnology has a firm connection with biological diversity as its genetic resources. The Living Modified Organism (LMO) that will be released to the free environtment will also affect the balance of the existing biological diversity. The regulation of biotechnology and its impact on biological diversity is at first mentioned on United Nation Conventions on Biological Diversity (UNCBD) 1992. This convention then has some protocols with specific issues. First, Cartagena Protocol on Biosafety to the Convention on Biological Diversity 2000 that regulates specifically about the transboundary transfer of Living Modified Organism (LMO). Second, The Nagoya Protocol on Access to Genetic Resources and the Fair and Equitable Sharing of Benefits Arising from Their Utilization 2010 focusing on the use of biological diversity as genetic resources. Third, Nagoya - Kuala Lumpur Supplementary Protocol on Liability and Redress to the Cartagena Protocol on Biosafety 2010 focusing on the regulations to anticipate the emerging impact on biological diversity as the consequence of the LMO’s transboundary transfer.Keywords : Interntional Law, Biotechnology, Biological Diversity